2019
DOI: 10.1007/s11606-019-04892-0
|View full text |Cite
|
Sign up to set email alerts
|

A National Survey of Undergraduate Clinical Education in Internal Medicine

Abstract: BACKGROUND: In the present milieu of rapid innovation in undergraduate medical education at US medical schools, the current structure and composition of clinical education in Internal Medicine (IM) is not clear. OBJECTIVE: To describe the current composition of undergraduate clinical education structure in IM. DESIGN: National annual Clerkship Directors in Internal Medicine (CDIM) cross-sectional survey. PARTICIPANTS: One hundred twenty-nine clerkship directors at all Liaison Committee on Medical Education acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Pincavage and colleagues examined the current structure of internal medicine clerkships via a national survey of clerkship directors. 10 The results revealed that over half of internal medicine clerkships do not require ambulatory training components. This raises important questions about the alignment, or lack thereof, of the clinical learning environments of medical student internal medicine clerkship education (inpatient predominant) and the likely skills and experiences needed to effectively deliver care in current and future complex health delivery systems.…”
Section: Clinical Learning Environmentmentioning
confidence: 99%
“…Pincavage and colleagues examined the current structure of internal medicine clerkships via a national survey of clerkship directors. 10 The results revealed that over half of internal medicine clerkships do not require ambulatory training components. This raises important questions about the alignment, or lack thereof, of the clinical learning environments of medical student internal medicine clerkship education (inpatient predominant) and the likely skills and experiences needed to effectively deliver care in current and future complex health delivery systems.…”
Section: Clinical Learning Environmentmentioning
confidence: 99%
“…In the paper entitled BUse of Simulated Patient Encounters to Teach Residents to Respond to Patients who Discriminate Against Health Care Workers,^Eisenberg and Kieffer provide education to firstyear internal medicine residents to improve skills in responding to an unfortunate growing trend, i.e., patients who exhibit discriminatory behavior towards members of the health care team. 4 The residents participated in a BResponding to Bias^workshop. After an instruction to frame an approach to respond, residents experienced four clinical scenarios with standardized patients covering gender bias, class bias, and racial bias.…”
Section: Curricular Components Of a Framework For Education On Biasmentioning
confidence: 99%
“…Interprofessional educators may be important facilitators of participatory and experiential learning experiences in appropriate settings. [3][4][5][6] Published online April 16, 2019…”
Section: Curricular Components Of a Framework For Education On Biasmentioning
confidence: 99%
“…6 In 2017, clerkship directors reported that time in GIM clinic ranged from 15 half days in the traditional block model to 31 half days as part of longitudinal integrated clerkships. 8 Despite increased attention to outpatient training in medical school, one IM residency program reported that only 15% of interns from a diversity of medical schools felt they received sufficient training in medical school to prepare them for their continuity clinic. 9 One possible reason for the discrepancy between increased medical school primary care curricula and discomfort with primary care among entering IM residents may be that existing training may be insufficient.…”
Section: Introductionmentioning
confidence: 99%